Case reportSkin melanoma associated with chronic lymphocytic leukaemia. Case report - Sobjanek, Michał; Szczerkowska-Dobosz, Aneta; Mital, Andrzej; Pęksa, Rafał; Toboła, Jacek; Włodarkiewicz, Adam (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2008)
Chronic lymphocytic leukaemia (CLL) is a low grade lymphoproliferative disorder that represents 25% of all leukaemias. Many investigations have confirmed the association between non-Hodgkin lymphoma (NHL) and secondary neoplasms, including melanoma malignum and non-melanoma skin cancer. We report a 61-year-old patient with metastatic melanoma that appeared 3 years after diagnosis of CLL.